(untitled) (Czech Journal of Multidisciplinary Innovations, 2023)
This research deals with the role of government spending and its role in achieving economic stability in Iraq during the period (2004-2020) by clarifying the concept of government spending, economic stability and the nature of stability. The research aims to analyze the relationship between government spending and economic stability in Iraq for the period (2004-2020). The study concluded that there is a relationship between spending and stability. A qualified private sector must be built to lead the economy and reduce the role of the state or carry out partnerships between the public sector and the private sector in preparation for playing a greater role. In achieving economic stability, as well as the immediate review of the structure of government spending and the rationalization of aspects of public expenditures by combating administrative and financial corruption.